Computer system for the study of problems of the distribution of values ​​of numerical sequences - Глазунов, Н. М.; Кравчук, И. В. (Problems of Informatization and Control, 2008)
The application of the computer system for the study of the distribution of values ​​of numerical sequences , as well as an agenda for further experiments and development of the project